THE SIGNIFICANCE OF HEART-TYPE FATTY ACID BINDING PROTEIN AMONG PATIENTS WITH ACUTE CORONARY SYNDROME - Kopytsya, N. P.; Kobets, A. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
With increasing numbers of patients with acute coronary syndrome (ACS) it is very important to have reliable biomarkers for early diagnostics and treatment. The role of heart-type fatty acid binding protein (H-FABP) is investigated to confirm patients with ACS and to evaluate the long-term prediction of complications and death. H-FABP allows to define myocardial infarction with changes on ECG and without ST elevation, it helps to differentiate unstable angina. H-FABP sensitivity is higher than troponin, myoglobin and other biomarkers, at the same time H-FABP has a high specificity. Increasing of the H-FABP level is an independent prognostic factor in the long-term prediction in patients with suspected ACS. H-FABP definition, especially in combination with other biomarkers, has the important value, when the diagnosis of ACS is difficult against the background of the atypical clinical picture, the absence of typical ECG changes.